SOCIAL STUDIES TEACHERS' PERCEPTIONS IN FACING THE INDEPENDENT CURRICULUM AT MTSN 2 MEDAN - mutiara hilda; Eka Susanti (SOSIOEDUKASI, 2026)
The independent curriculum has the characteristics of developing students' soft skills Through the Pancasila student profile strengthening project, focusing on essential materials to build Creativity and innovation of students in achieving basic competencies, and learning that Flexible is the flexibility for teachers to do learning according to the achievement stage And the development of each student. This research aims to find out Perception of IPS subject teachers on the implementation of the Independent Learning Curriculum, the obstacles faced by ips teachers in carrying out learning, as well as the solutions faced in facing the obstacles. This research Using a descriptive qualitative approach and data collection techniques through interviews, Observation, and documentation. The results of the study show a picture of perception, Obstacles and solutions applied by teachers in implementing the curriculum Independent. Teachers understand the principles of the curriculum such as teaching in the classroom And project-based learning, but still facing challenges in its implementation. Obstacles experienced include limited resources, difficulty adjusting methods Learning with student needs and infrastructure that lacks support in Madrasah, the solution in facing the obstacles is to participate in training or workshop and collaborate with teachers/teachers who are in mtsn 2 medan. This research concludes that the Independent Curriculum provides opportunities Innovation in learning, but requires increased support in the form of training Sustainable and development of tools/facilities and learning infrastructure. This research It is expected that it can be an input for the development of education policies in Indonesia and Support teachers throughout Indonesia.